Development of biology module on tissue culture material - Dewi, Kumala; Mellisa, Mellisa (Universitas Negeri Padang, 2023)
This study aims to produce modules on tissue culture material, which are valid. This research has three stages; analysis, design, and development. The instruments used were validation sheets and response questionnaires. The sampling technique is random. Retrieval of data using validation sheets and questionnaires. Data were analyzed using the scale method with a Likert modification. The validation results get an average of 87% (very valid). This module was well received by students in three schools with an average of 79.75% (good). Thus, the average percentage of all validators is 87.50% (very valid), and it is stated that the learning media developed are very valid.